The Coronavirus Pandemic (SARS-CoV-2): New Problems Demand New Solutions, the Alternative of Mesenchymal (Stem) Stromal Cells - Eiro, Noemi; Cabrera, Jorge Ruben; Fraile, Maria; Costa, Luis; Vizoso, Francisco J. (Frontiers in Cell and Developmental Biology, 2020)
Mesenchymal (stromal) stem cells (MSC) can be a therapeutic alternative for COVID-19 considering their anti-inflammatory, regenerative, angiogenic, and even antimicrobial capacity. Preliminary data point to a therapeutic effect of MSC in patients with COVID-19, and their effect seems based on the MSC's ability to curb the cytokine storm caused by COVID-19. In fact, promising clinical studies using MSC to treat COVID-19, are currently underway. For this reason, now is the time to firmly consider new approaches to MSC research that addresses key issues, like selecting the most optimal type of MSC for each indication, assuming the heterogeneity of the donor-dependent MSC and the biological niche where MSC are located. Another goal is to optimize the mass production of derivatives of the MSC secretome, which reproduces or magnifies the therapeutic effect of these cells. For all these reasons, we must integrate technologies such as immortalization or other genetic manipulations of the most appropriate MSC, the use of bioreactors that allow MSC growth in 3-D, together with the most optimal culture conditions, the use of adequate functional tests for these cells and the obtention of biological products derived from these cells, like extracellular vesicles and exosomes, before their clinical application. In addition, the incorporation of artificial intelligence tools can contribute to the proper integration of all this new emerging information.